A Study on Instructional Leadership Roles by Principals in Type 1AB and Type 1C Schools in Sri Lanka - Kumari, H. M. Lalitha (International Journal on Integrated Education, 2023)
The main purpose of this study was to examine how principals engage in instructional leadership roles in Type 1AB and Type C schools in Sri Lanka. The objectives of this study were to find out what kind of instructional leadership roles do principals in secondary schools in Sri Lanka play in promoting the education of students and upgrading the pedagogy of teachers, Identify how do teachers perceive leadership roles of principals in different categories of secondary schools in Sri Lanka and to find out what problems principals face when engaging in instructional leadership roles in secondary schools. The study was carried out in association with two hundred sample units of teacher and six school principals targeting to answer the research questions that were built. A mixed method approach was adopted. A questionnaire and interview schedules were used as data collection instruments. The data collected through the questionnaire were presented by using percentages and tables. The data collected through the interviews were analyzed by using thematic analysis. The findings revealed that a significant number of teachers (88%) in Type 1AB schools have positive perceptions about the instructional leadership roles principals engage in their schools. Also the findings indicated that the principals of type 1AB schools perform instructional leadership roles at a satisfactory level. However, the principals of 1-C schools do not perform instructional leadership roles at a satisfactory level due to the major challenge of having engaged in general administration roles than instructional leadership roles. It further revealed from this study that educational standards of the students in 1AB schools are higher than the educational achievements of students in Type 1-C schools. The study further revealed that the opportunities available for principals to acquire leadership training at an appropriate stage in their career are limited. It is, therefore, recommended that, the principals must be trained at an appropriate stage of their carrer in order for them to provide facilities for teachers professional development.